MORPHOMETRIC CHARACTERISTICS OF THE LIVER DURING PREGNANCY IN EXPERIMENTAL CHRONIC RENAL FAILURE - Rakhmankulova N.G., (Central Asian Journal of Medicine, 2025)
The treatment of liver pathologies in chronic renal failure observed during pregnancy and the prevention of their consequences remains a medical and social problem worldwide. Despite the development of methods for the prevention, diagnosis and treatment of liver diseases, mortality rates from them occupy leading places. Currently, in our country, special attention is paid to improving the quality of social protection and the health care system, diagnosis and treatment of chronic liver diseases. We studied the morphological and morphometric parameters of the liver of pregnant white rats. The main purpose of the study of post-chronic kidney disease changes in morphological and morphometric indicators of the liver of white-breed fetal rats.